CFD Investigation of MHTGR Natural Circulation and Decay Heat Removal in P-LOFC Accident - Wang, Chengqi; Sun, Xiaodong; Sabharwall, Piyush (Frontiers in Energy Research, 2020)
One of the key postulated accidents in a high-temperature gas-cooled reactor (HTGR) is the pressurized loss of forced cooling (P-LOFC) of the primary loop, which can be triggered by its primary helium circulator trip or turbine trip. If the reactor shutdown cooling system (SCS) fails during a P-LOFC accident, part of the reactor decay heat is absorbed by the reactor core materials and the rest removed by the reactor cavity cooling system (RCCS). In the extended period of P-LOFC accident, compounded with SCS failure, the core decay heat is supposed to be removed by conduction, natural circulation/convection, and radiation. Three-dimensional computational fluid dynamics (CFD) simulations were performed in this research to study the long-term heat removal mechanisms in the General Atomics' Modular High Temperature Gas-cooled Reactor (MHTGR) design during a P-LOFC accident. The reactor core temperature distribution and flow field were obtained at different decay power levels. The sensitivity of the natural circulation flow to the bypass gap width was investigated. The natural circulation flow intensity is relatively weak but very sensitive to the width of the bypass gaps.